The highway rehabilitation project = (The World Bank in Vietnam (WB), 2003)
The broader developmental goal of the Second Highway Rehabilitation Project is to raise overall economic efficiency and support the country's economic and social development through an improved transport infrastructure. The specific project objectives are: to reduce transport costs through improved national road infrastructure; to enhance efficiency by periodically maintaining the national road network; to reduce vehicle overloading and improve traffic safety; and to enhance the Ministry of Transport and Communication's institutional capacity in environmental impact assessment and monitoring. The project will comprise the following components: (1) Road maintenance and rehabilitation, that is, reconstructing part of a national highway and two major bridges; acquiring land, resettling and rehabilitating project-affected people, and providing supervision consultant services; (2) Periodic maintenance of selected priority national roads using contract services, and implementation of the new road maintenance management system; (3) Improvement of hazardous road sections, including measures to improve traffic safety; (4) Technical support to the Project Management Unit for Highway No. 1 (PMU1); (5) Support to the Vietnam Road Administration (VRA) and the Regional Road Management Unions (RRMU) to enhance institutional capacity; (6) Training trainers for the transport sector, strengthening local institutions, and enhancing the skills of highway sector manpower; and (7) Designing and preparing detailed bid and road engineering studies.